Allegro data-recording system based on MySQL database - Liu Tao; Fu Shenzhen; Zhang Zhu; Zhou Dong (Dianzi Jishu Yingyong, 2022)
In order to realize the functions of automatic acquisition, input and storage of PCB data by Allegro software, the secondary development of Allegro software based on SKILL language and the principle of IPC communication are studied. A data input system based on MySQL database is proposed and designed. According to the actual data access requirements and user permissions, the front-end data acquisition module and web page display module are designed. In the front-end data acquisition module, through the study of IPC communication, the communication protocol is formulated, and the communication interface is written with SKILL language and Python language to realize the communication between Allegro software and MySQL database. The web display module uses Java language to display and process the data. Finally, the function test of the data entry system is carried out, and the test results show that it can achieve the expected effect. The design of communication protocol between Allegro software and MySQL database, and the design of communication interface are the key design of the system. The realization of data acquisition module of the system has a strong reference value for the communication between Allegro software and other languages, and the function expansion of web page.